2017
DOI: 10.1007/s13538-017-0494-z
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating the Cuspidal Temperature Profile of a Non-equilibrium Chain

Abstract: In 1967, Z. Rieder, J. L. Lebowitz and E. Lieb (RLL) introduced a model of heat conduction on a crystal that became a milestone problem of non-equilibrium statistical mechanics. Along with its inability to reproduce Fourier's Law -which subsequent generalizations have been trying to amend -the RLL model is also characterized by awkward cusps at the ends of the nonequilibrium chain, an effect that has endured all these years without a satisfactory answer. In this paper, we first show that such trait stems from

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
3
0
2
Order By: Relevance
“…These boundary jumps represent the resistance offered to the heat transport due to the scattering of energy at the boundaries [21] and are not merely simulation effects. For F P U C chains, the boundary resistance is smaller because the collisions between the end thermostatted particles and the fixed boundary particles create an extra "pinning" effect [22]. Note that such reductions have been observed in collid-ing Φ 4 chains as well [8].…”
Section: Boundary Jumpsmentioning
confidence: 98%
“…These boundary jumps represent the resistance offered to the heat transport due to the scattering of energy at the boundaries [21] and are not merely simulation effects. For F P U C chains, the boundary resistance is smaller because the collisions between the end thermostatted particles and the fixed boundary particles create an extra "pinning" effect [22]. Note that such reductions have been observed in collid-ing Φ 4 chains as well [8].…”
Section: Boundary Jumpsmentioning
confidence: 98%
“…They showed that the temperature is approximately flat in the bulk of the chain (with deviations at the extremities [17]), with value (T L + T R )/2, instead of the linear temperature profile we would expect from Fourier's law (see figure 1.5). They also proved that the heat current in the chain is proportional to the temperature difference between both heat baths J ∝ (T L − T R ), instead of the temperature gradient, as in section 1.1, and hence κ ∝ N (diverging in the thermodynamic limit N → ∞).…”
Section: Thermal Conductivity Of Solidsmentioning
confidence: 98%
“…Adotando esta mudança, nota-se que as cúspides próximasàs extremidades vão se tornando mais suaves conforme o parâmetro de ancoragem de volume aumenta. As cúspides são eliminadas do perfil de temperaturas quando os acoplamentos atingem o limiar [62]: Capítulo 3. O papel das correlações entre as velocidades nos perfis de temperatura do sistema 39…”
Section: Figura 22unclassified
“…O papel das correlações entre as velocidades nos perfis de temperatura do sistema 41 k 1 ą k 1 crit 1 as cúspides voltam a surgir no sistema, mostrando que a presença da ancoragem de volumeé um fator necessário mas não suficiente para que o sistema não exiba tal característica em seu perfil de temperatura. O perfil semelhante ao modelo RLLé apresentado para todos os valores de k 1 inferiores a[62] de temperaturas bem suave próximoàs extremidades, marcando assim mais uma mudança de comportamento das partículas medianteà mudança de k 1 . A partir de então, para um crescimento contínuo do acoplamento das extremidades, nota-se que tal mudança tende a isolar as partículas 1 e N do restante da cadeia, de forma que o volume do sistema passa a interagir praticamente com si próprio, criando assim a caixa de fônons já descrita anteriormente.…”
unclassified